The last Puritans : mainline Protestants and the power of the past - Bendroth, Margaret, 1954- (University of North Carolina Press, 2015)
Congregationalists, the oldest group of American Protestants, are the heirs of New England's first founders. While they were key characters in the story of early American history, from Plymouth Rock and the founding of Harvard and Yale to the Revolutionary War, their luster and numbers have faded. But Margaret Bendroth's critical history of Congregationalism over the past two centuries reveals how the denomination is essential for understanding mainline Protestantism in the making. Bendroth chronicles how the New England Puritans, known for their moral and doctrinal rigor, came to be the antecedents of the United Church of Christ, one of the most liberal of all Protestant denominations today. The demands of competition in the American religious marketplace spurred Congregationalists, Bendroth argues, to face their distinctive history. By engaging deeply with their denomination's storied past, they recast their modern identity. The soul-searching took diverse forms -- from letter writing and eloquent sermonizing to Pilgrim-celebrating Thanksgiving pageants -- as Congregationalists renegotiated old obligations to their seventeenth-century spiritual ancestors. The result was a modern piety that stood a respectful but ironic distance from the past and made a crucial contribution to the American ethos of religious tolerance.